Evaluation of the effectiveness of Spirulina platensis for the nutritional rehabilitation of malnourished children aged 6–59 months: The case of the Mont-Ngafula II health zone - Mupemba Ngalamulume , Josué; Mufusama Koy Sita, Jean-Pierre; Kalenda Tshilombo , Nicodème; Batumbo, Doudou; Lusamba Ntumba , Séraphin Vinhy; Kiliyo, Lydie; Bakana Matsuela , Lucie; Tujibikila Mukuta, Adam (Orapuh Journal, 2026)
Introduction Childhood malnutrition remains a major public health challenge, particularly in resource-limited settings such as the Democratic Republic of the Congo (DRC). Effective, affordable, and sustainable nutritional interventions are urgently needed to improve the recovery of malnourished children. Spirulina platensis, a microalga with high nutritional density, represents a promising option; however, evidence from controlled trials in this context remains limited. Purpose To evaluate the nutritional effectiveness of Spirulina platensis supplementation on the nutritional status and biological parameters of malnourished children aged 6–59 months in the Mont-Ngafula II health zone in Kinshasa. Methods A single-blind randomised controlled trial was conducted among 100 malnourished children allocated to two groups over a 120-day period. One group received maize porridge enriched with spirulina (4 g every other day), while the control group received non-enriched maize porridge. Anthropometric indicators (mid-upper arm circumference, weight, and height) and biological parameters (haemoglobin, serum iron, albumin, total proteins, urea, and creatinine) were assessed before and after the intervention. Multivariate logistic regression was used to identify independent determinants of nutritional recovery. Results At the end of follow-up, 32% of children achieved complete nutritional recovery. The prevalence of severe acute malnutrition decreased from 71% to 47%. A highly significant improvement in mid-upper arm circumference was observed in the spirulina group (p < .001), along with significant increases in serum iron, albumin, and total protein levels. Spirulina consumption was strongly associated with nutritional recovery (OR = 357.2, 95% CI [5.24, 24,344.7], p = .006), with excellent model performance (AUC = 0.98). Conclusion Supervised supplementation with Spirulina platensis, integrated into a staple food, significantly improves both nutritional and biological status in malnourished children. This strategy appears well suited to resource-limited settings and merits thoughtful integration into child malnutrition management programmes, pending confirmation through larger-scale and longer-term studies.